2018
DOI: 10.1080/09593985.2018.1491080
|View full text |Cite
|
Sign up to set email alerts
|

Teaching professionalism: some features in Canadian physiotherapy programs

Abstract: The role of "professionalism" is core to many health professions including Physical Therapy (PT), and the development of competence in professionalism is a key requirement of entry-to-practice PT programs. However, the actual curriculum, teaching methodologies, and evaluation methods currently used to develop professional competence during PT training programs in Canada are unclear. This study explored current teaching practices, evaluation and curricular content related to professionalism in Canadian entry-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The frequency of communication-related topics in students' reflections also echoed OT and PT professions' emphasis on this concept. Previous research has reported that topics related to communication were emphasised in the Canadian physical therapy curriculum (Murphy et al, 2018) and in PT and PT settings (Adam et al, 2011;Hudon et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of communication-related topics in students' reflections also echoed OT and PT professions' emphasis on this concept. Previous research has reported that topics related to communication were emphasised in the Canadian physical therapy curriculum (Murphy et al, 2018) and in PT and PT settings (Adam et al, 2011;Hudon et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Professionalism is an evolving, socioculturally informed, multidimensional construct that encompasses behaviors and attributes expected of an occupational therapist by society [ 1 ]. Traditionally, professionalism was considered a competence that students would gain through spending time with role models in academic and clinical fields [ 2 ]. The definition of professionalism has recently come to include professional roles, professional identity, competencies, and responsibilities that support excellence in professional practice, leading to therapist-patient relationships, patient satisfaction, and healthcare outcomes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Determination and understanding the current levels of PTs' competency, not only provide a baseline information upon which to further develop using educational and professional development strategies, but also help to increase the competency levels and practice standards of the PTs (1) . Physical therapy education varies across the world (2) , but the demand for high-quality post-professional education remains the same (3) . The competency-based approach emphasizes outcomes relating to graduates' abilities, knowledge, and attitudes that will enable them to function as competent experts at the national or global level (4) .…”
Section: Introductionmentioning
confidence: 99%